6a squared-8ab+2a factor completely and check mentally
(2a - 3)(3a - 4)
It is: (2a+3)(3a+4) when factored
6a to the second power minus 8ab + 2a
Divide by 6a: 6a(a + 3b)
Since the question is 3(2a), then just write it out. 3(2a) is 2a+2a+2a or 6a.
6a2 - 8ab + 2aas you can see a is common to all terms. And 2 is a factor of 6,8, and 2. So 2a is a factor of all three terms:2a(3a-4b+1)
(2a - b)(2a + b)
If you mean -2a+6a then it simplifies to 4a
(a - 6)(2a + 3)
The GCF of 6a^2 and 8a is 2a.
5a-20+2a = 6a-11 5a+2a-6a = 20-11 1a = 9 a = 9
The value of a in the equation 5a plus 2a = 6-6a is a=6/11.
(7a - 1)(6a + 1)
-4 + 10 + 6a - 2a + 3 9 + 4a
2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b
2a*3 = 8+4a 6a = 8+4a 6a-4a = 8 2a = 8 a = 4
2a2 x 3a-3 = (2 x 3)a(2 + -3) = 6a-1
12a2b + 6a = 6a(2ab + 1)
= 2a - 10
(2a + b)(a + 3b)